Distribution of the AERONET site and radiation station in China selected in this study. - Hongfei Xie (6410837); Junfang Zhao (299684); Kaili Wang (2246485); Huiwen Peng (10739523) (2021)
Distribution of the AERONET site and radiation station in China selected in this study.